2020
DOI: 10.1016/j.jtherbio.2020.102705
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic changes following active heat acclimation

Abstract: Heat adaption through acclimatisation or acclimation improves cardiovascular stability by maintaining cardiac output due to compensatory increases in stroke volume. The main aim of this study was to assess whether 2D transthoracic echocardiography (TTE) could be used to confirm differences in resting echocardiographic parameters, before and after active heat acclimation (HA). Thirteen male endurance trained cyclists underwent a resting blinded TTE before and after randomisation to either 5 consecutive daily ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 54 publications
2
7
0
Order By: Relevance
“…We also did not measure the CONTROL groups training burden on the passive days in the HEAT group however cardiovascular strain was similar between groups. Echocardiography has signi cant inter-observer and intra-observer variability particularly in the measurement of LV volumes [75] which may explain why we were unable to demonstrate a signi cant increase in LVEDV in the HEAT group, in comparison to CONTROL, during this study in comparison to previous [71]. However we used the same echocardiographer to limit interobserver variability, who was blinded to the participants intervention.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We also did not measure the CONTROL groups training burden on the passive days in the HEAT group however cardiovascular strain was similar between groups. Echocardiography has signi cant inter-observer and intra-observer variability particularly in the measurement of LV volumes [75] which may explain why we were unable to demonstrate a signi cant increase in LVEDV in the HEAT group, in comparison to CONTROL, during this study in comparison to previous [71]. However we used the same echocardiographer to limit interobserver variability, who was blinded to the participants intervention.…”
Section: Discussionmentioning
confidence: 92%
“…Preliminary echocardiographic data [71]coupled with these data suggests improvements in diastolic function with heat acclimation above that of exercise alone. We know that exercise, regardless of weight loss, reduces occurrence and symptoms of atrial brillation and this is, in part, thought to mediated by improvements in diastolic dysfunction [72].…”
Section: Discussionmentioning
confidence: 92%
“…Recent human translational studies, using 1) Short-term isothermic heat acclimation achieved by cycling at a 32°C and 70% R.H. (Relative Humidity) at an exercise intensity of 2.0–2.7 W kg-1 for 5 days compared to daily cycling for 90 min, in temperate environmental conditions of 21.5°C and 36% R.H. and 2) Passive heat acclimation (12 d, −48°C, 50 min) ( Parsons et al, 2020 ; Wilson et al, 2020 ) indicated that short-term, active heat acclimation enhances ventricular compliance, along with physiological thermoregulatory responses (e.g., plasma volume expansion, decreased heart rate, altered cardiac filling pressure and increased stroke volume), rather than changes in cellular elasticity. No intrinsic cellular or molecular explanation for these responses were provided.…”
Section: Human Translational Studies On Left Ventricular Compliance A...mentioning
confidence: 99%
“…The impact of passive LTHA in rats confirms the findings of Horowitz et al (1986a) but differs from the effects of 5 days of passive HA in humans ( Trachsel et al, 2020 ), where minimal adaptive responses were detected in the heart. While Parsons et al (2020) and Trachsel et al (2020) , present pre versus post treatment comparisons within the same group, we performed within and between (namely, comparisons between all stressors employed) group analyses of the long-term impacts of the stressors, when hormonal responses (e.g., reduced thyroxin) leading to myosin phenotype changes take place ( Horowitz, 2003 ). Notably, the impact of seasonal temperatures on slow myosin were reported in Camelus dromedarius ( Abdelhadi et al, 2012 ).…”
Section: Human Translational Studies On Left Ventricular Compliance A...mentioning
confidence: 99%
“…For example, exercising Q has been reported to decrease (Wyndham, 1951), remain unchanged (Rowell et al, 1967;Wyndham et al, 1968), or increase (Nielsen et al, 1993) following HA, while data regarding human cardiac volumes, function and systemic blood flow is limited. Recently, passive and active HA regimens were shown to minimally enhance left atrial and ventricular diastolic volumes at rest; however, these responses were not correlated with an increase in BV or lowered HR (Parsons et al, 2020;Wilson et al, 2020). Passive HA with controlled hyperthermia has also failed to induce changes in resting HR, EDV, and SV in thermoneutral conditions (Trachsel et al, 2020).…”
Section: Hydration Strategy During Heat Acclimationmentioning
confidence: 99%